Análise técnica e econômica para a cultura do crisântemo de vaso submetida à distintas disponibilidades hídricas - Pereira, Anderson Crestani (2021)
Potted chrysanthemum is one of the most commercialized flower species in Brazil. However, there is little information related to correct water management and the economic viability of the production of the species. Thus, the present work sought to evaluate the behavior of the pot chrysanthemum, cultivating Cherry White, cultivated under different water managements and their respective productive and economic consequences. In addition to determining water consumption and obtaining cultural coefficients (Kc) for different reference evapotranspiration estimation equations (ETo). The experiment was conducted in a greenhouse in the Floriculture sector of the Polytechnic College of UFSM, Santa Maria - RS. A completely randomized design (DIC) was adopted, with five treatments based on the capacity of water retention of the vase (CRV) (40, 60, 80, 100 and 120% of the CRV), with 16 repetitions, each pot being one repetition. The determination of crop evapotranspiration (ETc) was done by weighing lysimeter, ETo was calculated by six different equations: Benevides-Lopez, Camargo, Linacre, Jensen-Haise, Hargreaves and Ivanov. Kc was obtained by the relationship between ETc and ETo. The following variables were measured: leaf area (cm²), plant height (cm), shoot dry mass (g), roots (g) and total dry mass (g), number of inflorescences per plant and the diameter of the inflorescences (cm). The classification of the commercial quality of the pots was stipulated according to the standards of the Brazilian Institute of Floriculture (IBRAFLOR). The results obtained showed that the water consumption of the crop increases as the availability of water increases. Average cultural coefficients of 0.98 were obtained for the vegetative phase, 1.29 from the beginning of the reproductive phase to the point of commercialization and then 0.85 until the end of the reproductive phase. The best results of development and production of the plants were observed when carried out in the range of 80% to 100% of the maximum vessel retention capacity. The maximum technical and economic efficiency of the production of commercial chrysanthemum vases was obtained with a 226.29 mm depth, corresponding to 92.25% of the water retention capacity of the vase.